MODERNIZATION BREAKTHROUGH OF THE NORTH CAUCASUS IN THE IMPERIAL AND SOVIET PERIODS: FROM PROGRESS TO THE CATASTROPHE - Yu. Yu. Klychnikov (Гуманитарные и юридические исследования)
The article studies the stages of modernization in the North Caucasus, which took place in the XIX-XX centuries. The successes and failures of the process are specified. The representatives of the Russian (Soviet) administration had to solve the most challenging tasks. The spheres, which were viewed as the most perspective as regards the enhancement of the local people life, are demonstrated. The article shows the role of the Russian (and more generally - theSlavic) ethnos in providing the population of the region access to the values of a modernized society. The vul- nerability (including the physical one) of the Russian population in the periods of the archaic institutes renewal in the North Caucasus is shown. The domination of archaic or modern in the local practice reveals alternation. Such situation mostly depends on state institutes effectiveness, which to a considerable extent act as initiators of innovations in the region.